The Parent Company's Influence on the Subsidiary's Generic Strategy - Krzysztof ĆWIK (Communications of International Proceedings, 2022)
The business group is a specific type of an economic entity, because subsidiaries must achieve goals, which are a consequence of their role in the group and their supervisory board (board of directors), in addition to obligations under the law, may engage to the management of subsidiary in many different ways. There are three generic types of subsidiaries: operational, cooperative and conglomerate. The results of the research showed, due to the nature of mutual relations between parent and subsidiary entities and the degree of required coordination of the subsidiary’s activities by the parent entity, the greatest influence of the parent entity on the subsidiary’s strategy was in the case of operating-type entities; its smaller scope was noticeable in entities such as conglomerate, and the lowest in financial-type entities. The scope of this impact was measured by identifying the elements of the strategy whose content stems from the opinions and recommendations of the parent company.
Keywords: Parent Company; Subsidiary; Business Group; Strategy